Formulasi Bakteri Endofit Akar Kedelai untuk Pengendalian Pustul Bakteri - Trimurti Habazar; Zurai Resti; Yulmira Yanti; Sutoyo Sutoyo; Imelda Imelda (Jurnal Fitopatologi Indonesia, 2015)
Two isolates of bacterial endophyte from soybean root were found to be effective to control bacterial pustule caused by Xanthomonas axonopodis pv. glycines. Formulation of the bacterial isolates is required to maintain the effectivity of this bacterial isolates during storage, transportation and application. The aim of this research was to obtain the best carrier for formulation to maintain the effectivity of bacterial endophyte in storage to control bacterial pustule on soybean. Three kind of carrier agent was evaluated for formulation of bacterial endophyte i.e. peat soil, tapioca flour and coconut water + 1% palm oil. Each carrier agent was combined with 5 treatment of storage time i.e. 0, 1, 3, 5 and 7 weeks. Soybean plants was inoculated by. X. axonopodis pv. glycines 2 weeks after planting by rubbing bacterial suspension (106 cel mL-1) on lower surface of leaves. The results showed that all formulas of bacterial endophyte were able to suppress the bacterial pustule on soybean. The best formulations were bacterial endophyte in peat soil stored for 1 and 7 weeks (effectivity rate 79.85% and 77.02%) and coconut water + palm oil and storaged for 3 weeks (effectivity rate 77.46%).